OVERCOME THE PROBLEM OF DEVIANT BEHAVIOR THROUGH GROUP GUIDANCE TECHNIQUES FOR JUNIOR HIGH SCHOOL STUDENTS - Rahman, Syahnur (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Â Â Â ABSTRAK: The main problem in this research is to overcome the low ability of students to solve problems., Which almost every day many problems that arise such as: personal, social, career and even learning difficulties. The sample in this study, namely 7th grade SMP 12 Malang. The results of the assessment appear in table 4.3 which states "I feel a loss if I do not go to school" shows the 35% increase in cycle II to 59%. Besides that, based on the analysis of observational data at the time of the action, it can be seen in the average results of students’ understanding of behavior during the first cycle of 5.83 and at the meeting of the first 2 cycles there was an average increase of slightly to 6.5 Similarly the average results at the meeting 3 is 7 and at the 4th meeting of the second cycle II the average value of the assignment (post test) was 8.3. Â Â Â Â Â Â Â Based on the findings of this study it is suggested to the Guidance and Counseling Teachers to apply group guidance techniques in alleviating student problems. With the use of group guidance on students, it can help enlighten the problem in accordance with the group guidance goals referred to in this study.